97.5k views
4 votes
Please help solve this problem

Please help solve this problem-example-1
User Enkhbat
by
6.1k points

2 Answers

3 votes

Answer:

The correct answer is option B. 2√6

Explanation:

It is given that an expression, 6√2/√3

To simplify the expression

6√2/√3

Multiplying numerator and denominator with √3

6√2/√3 = (6√2 x √3)/(√3 x √3)

= [ 6 x √(2x3)]/3) (√2 x √3 = √(2 x 3)

= 6√6/3

= 2√6

Therefore the simplified form of given expression 6√2/√3 is 2√6.

The correct answer is option B. 2√6

User Idij
by
6.6k points
4 votes

Answer: OPTION A

Explanation:

To simplify the expression you must multiply the numerator and the denominator of the expression by √3.

As all the square roots have equal index, you can multiply the radicands, which are the numbers inside of the sqaures roots.

You also must keep on mind that:


(\sqrt[n]{a})^n=a

Therefore, you obtain:


(6√(2)*√(3))/(√(3)*√(3))=\frac{6\sqrt[]{6}}{3}=\frac{2\sqrt[]{6}}{3}

User PaperThick
by
5.4k points